Indian Horse - Pollon, Casey Shea (MacEwan University Student eJournal, 2015)
Type as Image: Eliciting Emotions is a project of VCDE233 Typography II (Constanza Pacher) and VCDI223 Design and Pre-Press Production (Jess Dupuis), both courses in the Design Studies Diploma Program at MacEwan University. Students were asked to capture the essence of the book Indian Horse, by Richard Wagamese, and translate it into a three-poster series using typography as the main element. Under the premise that the visual form is dictated by the content, students were encouraged to analyze plot, characters, point of view, imagery, tone, themes and symbolism to extract key words, sentences and passages as the basis for their designs. Students were asked to challenge literal interpretations by exploring the use of expressive typography and text and image relationships.